Custodians of carbon: creating a circular carbon economy - Newman, Alex J. K.; Dowson, George R. M.; Platt, Edward G.; Handford-Styring, Hannah J.; Styring, Peter (Frontiers in Energy Research, 2023)
To stand a chance of achieving net zero greenhouse gas emissions and in the implementation of UN Sustainable Development Goals (SDGs), society must move away from being consumers of carbon to being custodians. While SDG 7 focuses on clean energy, chemicals and materials are themselves energy, energy stored in chemical bonds. Behavioural change is needed to appreciate the societal value of carbon and recycle carbon already present in the environment, so extracting more fossil carbon from the Earth is avoided. Society should develop new technologies such as carbon capture and utilisation to create value-added products, not waste. To be effective, the social impact of change must be considered, its effect on the environment, and whether this transition makes economic sense. If there is social injustice, new approaches are needed. If there is no environmental benefit, interventions must be reconsidered. This becomes an iterative process seeking to achieve the best-balanced scenarios. As new technologies develop, interventions by governments providing aid to subsidise and accelerate new technologies will be needed. Care must be taken to ensure fiduciary duty is applied so the best possible use of public money is delivered. In this paper a systems approach is taken in developing a new circular carbon economy, where models are developed to include lifecycle, techno-economic, and social impact assessment studies into any policy development and commercialisation plans. It is vitally important to develop this methodological thinking early in that planning phase to avoid serious errors that could be costly financially, socially and environmentally. In early stages of development, a coarse-grained approach is required focusing on hotspot analysis. Once hotspots have been identified, finer grained analysis can be undertaken to develop rational approaches to process and policy development. It is vitally important that all disciplines are included within the development of such models, relying not only on engineers and scientists, but also social scientists, psychologists and financial experts. If such an approach is developed now, there is a good chance of identifying acceptable pathways to achieving sustainable development goals. This paper addresses gaps in the CO2 utilisation where social and fiscal issues are often overlooked.